1996
DOI: 10.1164/ajrccm.154.5.8912754
|View full text |Cite
|
Sign up to set email alerts
|

An epidemiologic investigation of asthma in welders.

Abstract: To clarify whether asthma may be caused by fume from welding mild steel and to evaluate the possible strength of such an effect, we quantified airway responsiveness among young shipyard workers with different levels of fume exposure. Clinical investigation comprised a cross-sectional survey of 19- to 27-yr-old workers who were completing 3 to 9 yr of employment in various trades, and a control group of 15- to 17-yr-old school leavers who were applying for apprenticeships within the same trades. Both groups wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
1

Year Published

1998
1998
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(30 citation statements)
references
References 25 publications
1
28
0
1
Order By: Relevance
“…Fumes or hazards produced during the welding process cause various health-related complications including respiratory disease and asthma. In this regard, previous studies have reported that fumes of welding exposure might be a cause of asthma [10][11][12]. In current finding, the incidence of respiratory disease was 20.45%.…”
Section: Discussionsupporting
confidence: 50%
“…Fumes or hazards produced during the welding process cause various health-related complications including respiratory disease and asthma. In this regard, previous studies have reported that fumes of welding exposure might be a cause of asthma [10][11][12]. In current finding, the incidence of respiratory disease was 20.45%.…”
Section: Discussionsupporting
confidence: 50%
“…Asthma was diagnosed in 124 of 246 new cases of occupational lung diseases in welders reported by Ross et al [18]. According to Beach et al [19], approximately 1% of welders were likely to develop occupational asthma after 5 years of work. Most studies estimated 2-3.2% of all cases of occupational asthma as welding related asthma.…”
Section: Discussionmentioning
confidence: 99%
“…Det har lenge vaert kjent at sveising på rustfritt stål gir økt risiko for astma. Man har imidlertid også funnet holdepunkter for at sveisere generelt har økt risiko for å utvikle irritantutløst astma (10).…”
Section: Tiltakunclassified